2005
DOI: 10.1620/tjem.207.249
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Amifostine on Adriamycin-Induced Acute Cardiotoxicity in Rats

Abstract: Free oxygen radicals and lipid peroxidation are responsible for adriamycin-induced cardiotoxicity. Amifostine is a scavenger of free radicals and may function as a selective cytoprotective agent. The aim of this study was to investigate the effects of amifostine on adriamycin-induced lipid peroxidation and the levels of protective enzymes in the heart. Male Wistar rats were randomly allocated to three groups: pretreated, untreated, and control (n = 10 in each group). Rats were pretreated with an intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…The effects of doxorubicin on GSH and protective enzymes such as catalase, Gpx and SOD are controversial a :p < 0.001 as compared to control group, b :p < 0.05 as compared to control group, c :p < 0.05 as compared to MITO-2.5 group, d :p < 0.001 as compared to MITO-2.5 group, e :p < 0.01 as compared to control group, f :p < 0.005 as compared to MITO-2.5 group, g :p < 0.005 as compared to control group, h :p < 0.001 as compared to AMI group [9,11,12,33,34]. Although MITO induced lipid peroxidation and the generation of free oxygen radicals in liver microsomes [3,8,18], there are only a few experimental studies in which these effects in the heart are demonstrated [22,23].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The effects of doxorubicin on GSH and protective enzymes such as catalase, Gpx and SOD are controversial a :p < 0.001 as compared to control group, b :p < 0.05 as compared to control group, c :p < 0.05 as compared to MITO-2.5 group, d :p < 0.001 as compared to MITO-2.5 group, e :p < 0.01 as compared to control group, f :p < 0.005 as compared to MITO-2.5 group, g :p < 0.005 as compared to control group, h :p < 0.001 as compared to AMI group [9,11,12,33,34]. Although MITO induced lipid peroxidation and the generation of free oxygen radicals in liver microsomes [3,8,18], there are only a few experimental studies in which these effects in the heart are demonstrated [22,23].…”
Section: Discussionmentioning
confidence: 93%
“…Catalase, SOD and Gpx play critical roles in protecting the myocardium from lipid peroxidation and free oxygen radicals under oxidative damage. It was detected in some experimental studies that doxorubicin and idarubicin decreased GSH, catalase, Gpx, and SOD levels in the heart tissue [9,11,37,38]. However, over-expression of catalase and Mn-SOD activities were detected after doxorubicin administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protection from cisplatin nephrotoxicity and ototoxicity has been shown, as well as protection of peripheral neural tissue from cisplatin, paclitaxel, vincristine and vinblastine toxicity. However, data concerning amifostine efficacy in preventing the toxic effects of DOX are still insufficient (Bolaman et al, 2005;Dobric et al, 1998;Dragojevic-Simic et al, 2004;Nazeyrollas et al, 1999;Potemski et al, 2006). As previously mentioned, amifostine uptake has been documented to be relatively high in normal tissues compared with experimental tumors.…”
Section: Amifostinementioning
confidence: 99%